Alternanthera ebracteolata (Amaranthaceae), a new species from Kerala (SW-India) - Arya, Sindhu; Anilkumar, Venugopalan Nair Saradhamma (Phytotaxa, 2021)
A new species of Alternanthera from the northern region of Kerala (India)―Alternanthera ebracteolata―is described and illustrated. Morphological description as well as original photographs and drawings are provided. A. ebracteolata is morphologically similar to A. tenella from which differs by the peduncled inflorescence, number of flowers per glomerule, shape and colour of the bracts, absence of bracteoles, shape and color of appendages on androecial tube, and shape of seeds.